Effect of perioperative opioids on cancer recurrence: a hypothesis. (August 2010) - Singleton, Patrick A; Moss, Jonathan
The possibility that anesthetic drugs can influence cancer recurrence rate is a subject of recent interest. Based on early in vitro data demonstrating opiates on breast cancer xenografts and two recent epidemiologic studies suggesting differences in recurrence rates in both breast and prostate cancer contingents dependent on whether patients received a combined regional–general anesthetic or a general anesthetic with opioid analgesia, there has been recent interest in the role of the µ-opioid receptor (MOR) in angiogenesis and oncogenic signaling. We recently demonstrated that morphine causes reciprocal transactivation of the MOR and VEGF receptors and that MOR-knockout mice do not develop significant tumors when injected with lung cancer cells as do their wild-type controls. Furthermore, infusion of the peripheral MOR antagonist methylnaltrexone markedly attenuates tumor growth in experimental mouse models. These experimental data support the hypothesis that opioids affect tumor progression and suggest the MOR as a potential target for chemotherapeutic drugs.